Dampak Penggunaan E-bekal Terhadap Santri Nurul Jadid - Moh Hamzah; Hasanah Hasan; Sundussiyah Sundussiyah; Wafiqah Wafiqah; Anisa Nava Tidar (CV. Akira Java Bulu, 2025)
The transition from the traditional era to the digital era has brought significant changes in various aspects of life, including the transaction system. Nurul Jadid Islamic Boarding School, as one of the oldest Islamic educational institutions in Indonesia, has adopted technological innovations in the form of an electronic payment system known as E-Bekal. This study aims to analyze the benefits, influences, and challenges in the implementation of E-Provision on the lives of students in the pesantren. The research method used is a qualitative approach with literature study techniques. The results of the study show that E-Bekal makes a significant contribution to transaction efficiency, student financial management, and control of consumptive behavior, with an influence of 83.7% on students' buying interest. In addition, this system helps guardians of students in monitoring their children's finances more transparently. However, several obstacles were identified, such as the limitation of the use of cards outside the pesantren, dependence on internet access, and lack of understanding of technology among users. This research recommends the development of the E-Bekal system to be more flexible, improving technological infrastructure, and educating users to optimize its benefits. With these steps, E-Bekal is expected to be a sustainable innovative solution in supporting the modernization of Islamic boarding schools in the digital era.